Renewable Energy Potentials In Cameroon: Prospects and Challenges - Asan Vernyuy, Wirba; Abdullahi, Abubakar Mas'ud; Firdaus, Muhammad-Sukki; Salman, Ahmad; Razman, Mat Tahar; Ruzairi, Abdul Rahim; Abu Bakar, Munir; Md Ershadul, Karim (Elsevier Ltd, 2015)
This paper aims at discussing the renewable energy potentials in delivering parts of the energy needs in Cameroon. The country has an enormous renewable energy potential. The lack of clear renewable energy policy in the mix is an issue that needs to be addressed urgently by the Cameroonian government policy makers. The absence of commitment and enthusiasm from the government is weakening the sector potentiality to be developed either by private sector investments and also foreign investors. Solar, wind and thermal energy plants are essential to meet the electrification of Cameroon.